2022
DOI: 10.3390/jcdd9070202
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence and Belief about Medication among Vietnamese Patients with Chronic Cardiovascular Diseases within the Context of Implementing Measures to Prevent COVID-19

Abstract: Background: Long-term adherence is crucial for optimal treatment outcomes in chronic cardiovascular diseases (CVDs), especially throughout the COVID-19 wide-spreading periods, making patients with chronic CVDs vulnerable subjects. Aim: To investigate the relationship between the characteristics, beliefs about prescribed medication, COVID-19 prevention measures, and medication adherence among patients with chronic CVDs. Methods: This is a cross-sectional study of outpatients with chronic CVDs in Southern Vietna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…42 A study of Vietnamese patients with chronic cardiovascular diseases found that rural life was significantly associated with poor drug adherence. 43 This may be due to the different population characteristics between the two studies, in which the location factor (rural or urban) was…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 A study of Vietnamese patients with chronic cardiovascular diseases found that rural life was significantly associated with poor drug adherence. 43 This may be due to the different population characteristics between the two studies, in which the location factor (rural or urban) was…”
Section: Discussionmentioning
confidence: 99%
“…shown as an association with medication adherence. 18,42,43 In a study, it was seen that stress due to living in houses without terraces or courtyards during the COVID-19 pandemic was likely to cause seizures and behavioral deterioration. 18 In a study, it was found that the leading causes of high stress experienced by epilepsy patients were social problems, fear of infection, and financial issues.…”
Section: Discussionmentioning
confidence: 99%